Meningkatkan Keterampilan Berpikir kritis Siswa Dengan Menggunakan Model Problem Based Learning Di Kelas V SDN Sungai Rangas - Meysha Pradella; Tika Puspita Widya Rini (CV. ITTC INDONESIA, 2024)
The problem in this study is the low critical thinking skills of students in science content. This is due to the learning process that tends to be monotonous, lack of student curiosity, lack of variety in learning models, learning is not student-centered, and students' critical thinking skills have not been raised. Efforts to overcome this by using Problem Based Learning model. This research used PTK which was carried out in 4 meetings. The purpose of this study was to analyze students' critical thinking skills. Data collection of critical thinking skills was obtained through rubric and observation sheets. The results showed that critical thinking skills at meetings 1 to 4 have increased from 47% to 95% with very skillful criteria. Based on the results of this study, it can be concluded that the use of Problem Based Learning model can improve students' critical thinking skills.